2014
DOI: 10.1111/liv.12613
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vasoactive proteins in gastric antral mucosa reflects vascular dysfunction in patients with cirrhosis and portal hypertension

Abstract: This is the first evidence that the expression of vasoactive proteins in mucosa from the gastric antrum of patients with cirrhosis reflects their vascular dysfunction and possibly changes after therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In any case, patients receiving TIPS were found to have an amelioration of PHG and a reduced requirement for blood transfusion, thus supporting a beneficial role of ther- 8 Portal hypertensive gastropathy is associated with iron deficiency anemia K original article apeutic options aiming at reducing portal pressure for the treatment of PHG [27]. Furthermore, the beneficial effect of HVPG reduction on PHG is further promoted by lower expression of vasoactive proteins in gastric mucosal biopsies in humans upon TIPS [53] and NSBB treatment [54].…”
Section: Discussionmentioning
confidence: 91%
“…In any case, patients receiving TIPS were found to have an amelioration of PHG and a reduced requirement for blood transfusion, thus supporting a beneficial role of ther- 8 Portal hypertensive gastropathy is associated with iron deficiency anemia K original article apeutic options aiming at reducing portal pressure for the treatment of PHG [27]. Furthermore, the beneficial effect of HVPG reduction on PHG is further promoted by lower expression of vasoactive proteins in gastric mucosal biopsies in humans upon TIPS [53] and NSBB treatment [54].…”
Section: Discussionmentioning
confidence: 91%
“…Earlier findings have demonstrated that TIPS renders a 100% hemodynamic response to NSBB [25]. Interestingly, this effect might be due to improved signaling in the mesenteric bed, which was shown recent new data [23,24]. Since the NSBB response protects from variceal bleeding and decreases bacterial translocation and ACLF [10,18], TIPS might be an additional tool in overcoming the pathophysiological mechanisms in liver cirrhosis with severe portal hypertension, which render NSBB ineffective.…”
Section: Tips and Its Hemodynamic Changesmentioning
confidence: 92%
“…Significantly, systemic activation of vasoconstrictor systems is normalized within six months. Similarly, alterations to intracellular signaling pathways (expression and activation of vasoactive proteins) in different vascular regions lead to better vasoconstriction [22][23][24]. Earlier findings have demonstrated that TIPS renders a 100% hemodynamic response to NSBB [25].…”
Section: Tips and Its Hemodynamic Changesmentioning
confidence: 99%
“…Staining for CD31+ and α-SMA was performed in cryosections from liver tissue (3μm and 7μm thickness, respectively) as described previously [ 51 53 ]. Briefly, after several steps, cryosections were incubated with a mouse anti-SMA antibody (clone 1A4; Sigma-Aldrich, Munich, Germany) or with antibody against CD31+ (ab24590, Abcam, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%